STRATEGI PENGELOLAAN KELAS BAHASA INGGRIS SELAMA PANDEMI COVID-19 - Aslamiah, Suaibatul (STIT Ibnu Rusyd Tanah Grogot, 2021)
Classroom management in the teaching and learning process is very important, especially at this time. To ensure that learning goes well, the teacher should know how to manage the classroom properly and correctly. This journal discusses about how to manage classes, the objectives of class managements, the principles of classroom management, the classroom management strategies during covid 19 and strategies for managing English classes. The purposes of classroom management are to build student’ enthusiasm and creativity, build conducive situations and condition, provide and manage facilities, foster and guide students. The principle of classroom management is influenced by internal and external factors of students, emotions, thoughts, and behavior. Moreover, the flexibility, warmth, interest, creativity and discipline of teachers.Classroom management strategies during the covid 19 pandemic include habituation from offline learning to online classes, short, concise and clear using Pdf or video tutorials, class discussions, groups and collaborationbetween teachers and parents. English classroom management strategy is to use the edutainment learning method and the application of quizziz, kahoot,dou lingo and word puzzle.Keyword: classroom management, online learning, english learning